Operando double-edge high-resolution X-ray absorption spectroscopy study of BiVO4 photoanodes - Alberto Piccioni; Jagadesh Kopula Kesavan; Lucia Amidani; Raffaello Mazzaro; Serena Berardi; Stefano Caramori; Luca Pasquini; Federico Boscherini (Journal of Synchrotron Radiation, 2024)
High energy resolution fluorescence detected X-ray absorption spectroscopy is a powerful method for probing the electronic structure of functional materials. The X-ray penetration depth and photon-in/photon-out nature of the method allow operando experiments to be performed, in particular in electrochemical cells. Here, operando high-resolution X-ray absorption measurements of a BiVO4 photoanode are reported, simultaneously probing the local electronic states of both cations. Small but significant variations of the spectral lineshapes induced by the applied potential were observed and an explanation in terms of the occupation of electronic states at or near the band edges is proposed.